Essentials of stem cell biology - Lanza, Robert, 1956- (Academic Press, 2009)
First developed as an accessible abridgement of the successful Handbook of Stem Cells, Essentials of Stem Cell Biology serves the needs of the evolving population of scientists, researchers, practitioners and students that are embracing the latest advances in stem cells. Representing the combined effort of seven editors and more than 200 scholars and scientists whose pioneering work has defined our understanding of stem cells, this book combines the prerequisites for a general understanding of adult and embryonic stem cells with a presentation by the world's experts of the latest research information about specific organ systems. From basic biology/mechanisms, early development, ectoderm, mesoderm, endoderm, methods to application of stem cells to specific human diseases, regulation and ethics, and patient perspectives, no topic in the field of stem cells is left uncovered. * Contributions by Nobel Laureates and leading international investigators * Includes two entirely new chapters devoted exclusively to iPS written by the scientists who made the breakthroug * Edited by a world-renowned author and researcher to present a complete story of stem cells in research, in application, and as the subject of political debate.